El Excentrico, 1971-08-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
August 5, 1971 [5 de agosto de 1971]. No volume or issue number. Cover has a photograph of model Rita Herrera, "A GO! GO! Dancer" taken by photographer Bobby Diaz.